Fresno-Merced Counties Legal Services: Baby Shower for Stephanie Leifer - Watkins, Howard::::::::: (1979)
Janie Munoz, Eddie Mae Lomack, Verletz Hooks, William Leifer, Nancy Currier, Cindy Calvert, Judy Evans Potluck in office library